Protective Effects of Mogroside V on Oxidative Stress Induced by H2O2 in Skin Fibroblasts - Mo Q; Fu H; Zhao D; Zhang J; Wang C; Wang D; Li M (Dove Medical Press, 2021)
Qiuting Mo, 1, 2 Hao Fu, 1, 2 Dan Zhao, 1– 3 Jiachan Zhang, 1– 3 Changtao Wang, 1– 3 Dongdong Wang, 1, 2 Meng Li 1, 2 1Beijing Key Laboratory of Plant Resource Research and Development, College of Chemistry and Materials Engineering, Beijing Technology and Business University, Beijing, People’s Republic of China; 2Institute of Cosmetic Regulatory Science, Beijing Technology and Business University, Beijing, People’s Republic of China; 3Beijing Advanced Innovation Center for Food Nutrition and Human Health, Beijing Technology and Business University, Beijing, People’s Republic of ChinaCorrespondence: Dongdong Wang; Meng Li Tel/Fax +86-010-68984917Email Wdd@btbu.edu.cn; limeng@btbu.edu.cnPurpose: Damage caused by oxidative stress leads to the premature aging of cells. Mogrosides, the main active components of Siraitia grosvenorii, have strong antioxidant activity; however, it is unclear whether mogroside V (MV) exerts these effects in skin cells. This was investigated in the present study by evaluating the protective effects of MV against oxidative damage induced by hydrogen peroxide (H 2O 2) in skin fibroblasts.Methods: Mouse skin fibroblasts (MSFs) were treated with H 2O 2 and cell viability, total antioxidant capacity, reactive oxygen species (ROS) production, malondialdehyde (MDA) content, and antioxidant enzyme activity were assessed.Results: Treatment with MV reduced the ROS level and MDA content in MSFs treated with H 2O 2. This was accompanied by increased superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) activities.Conclusion: MV reduces H 2O 2-induced oxidative stress and enhances endogenous antioxidant activity in skin fibroblasts. Thus, MV can potentially be used as an ingredient in anti-aging cosmetic products.Keywords: Siraitia grosvenorii, mogroside V, oxidative stress, antioxidant